THE EFFECT OF WORK ENVIRONMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT THE SUNGAI PENUH CITY BAPPEDA OFFICE - Sudirman, Sudirman (JURNAL ILMU MANAJEMEN, 2023)
One of the benchmarks of good performance is a high level of discipline, however, the Regional Planning and Development Agency (BAPPEDA) of Sungai Penuh City faces problems in improving the performance of its employees despite implementing strict regulations. This study aims to: 1) analyze the influence of the Work Environment on the performance of BAPPEDA Office Employees of Sungai Penuh City; 2) analyze the effect of Job Satisfaction on the performance of BAPPEDA Office Employees in Sungai Penuh City; 3) analyze the effect of the Work Environment on work motivation at the Sungai Penuh City BAPPEDA Office; 4) analyze the effect of Job Satisfaction on the Work Motivation of BAPPEDA Office Employees in Sungai Penuh City; 5) analyze the effect of work motivation on the performance of BAPPEDA Office Employees in Sungai Penuh City. The population in this study is all employees of the Sungai Penuh City BAPPEDA Office which amounts to 37 people. The sample in this study was all 37 employees of the Sungai Penuh City BAPPEDA Office. The data analysis tool used is path analysis at an alpha level of 0.05. Based on the results of the study shows that: the work environment has a positive and significant effect on employee performance; job satisfaction has a positive and significant effect on employee performance; the work environment has a positive and significant effect on employee motivation; job satisfaction has a positive and significant effect on employee motivation; Work motivation has a positive and significant effect on the performance of employees of the Sungai Penuh City BAPPEDA Office.